Pengaruh Budaya Organisasi dan Personaliti Terhadap Konflik Kerja: Satu Kajian ke atas Anggota Polis Diraja Malaysia (PDRM) dan Angkatan Tentera Malaysia (ATM) - Nozri, Senawi (2013)
Cooperation crime prevention patrols carried out by the police and the ATM is one step in the Blue Ocean Strategy to reduce the crime index for meeting the goals of national priority areas or better known as the National Keys Result Area (NKRA). The research conducted was to determine the influence of organizational culture and personality conflicts that occur during collaborative work was conducted among members of the patrol police and ATM. Respondents were members of the police and the implementing ATM patrols in 11 selected major cities throughout Malaysia. As the police and the ATM is two different security organizations in principle and have the organizational culture as well as members of different personalities, it is assumed these patrols cooperation will result in conflict. The results showed that there are indeed significant differences in the organizational culture and personality between the police and members of the ATM which explains more about the difference these two organizations, especially when it comes to the purpose of this organization exists. Police are more focused on national security while working ATM to keep our sovereignty from the threat of other countries have a way of training and the formation of different organizations. However, organizational culture and personality differences between members of the police and the ATM were not giving rise to serious conflicts during their patrols working to prevent crime. This is due to a weak negative relationship between organizational culture and personality to work conflicts. This means that if a member of the police or ATM adopt the concept of a strong organizational culture or to focus more and have a positive personality trait then it will reduce the conflicts of work going on